Корреляционный подход к оценке критической температуры хрупкости материалов корпусов реакторов ВВЭР1000 в необлученном состоянии - Ревка, В.Н. (Ядерна та радіаційна безпека, 2015)
Проведен статистический анализ данных по 10 энергоблокам ВВЭР-1000 АЭС Украины для получения корреляционного соотношения между критическими температурами хрупкости Тк0 (по паспорту корпуса реактора) и Тки (по результатам испытаний образцов-свидетелей) основного металла и металла сварного шва в необлученном состоянии. Анализ показал, что увеличению температуры Тки сопутствует увеличение Тк0 и эта взаимосвязь является линейной для исследованных материалов. В рамках представленного корреляционного исследования предложена формула для оценки температуры Тк0, которая может быть использована для определения с необходимым уровнем консерватизма критической температуры хрупкости материалов при обосновании безопасной эксплуатации корпуса реактора ВВЭР-1000. Проведено статистичний аналіз даних по 10 енергоблоках ВВЕР-1000 АЕС України для отримання кореляційного співвідношення між критичними температурами крихкості Тк0 (за паспортом корпусу реактора) та Тки (за результатами випробувань зразків-свідків) основного металу та металу зварного шва в неопроміненому стані. Аналіз показав, що збільшення температури Тки супроводжується зростанням Тк0 і цей взаємозв’язок є лінійним для досліджуваних матеріалів. У рамках наведеного кореляційного дослідження запропоновано формулу для оцінки температури Тк0, що може бути використана для визначення з необхідним рівнем консерватизму критичної температури крихкості матеріалів у процесі обґрунтування безпечної експлуатації корпусу реактора ВВЕР-1000. A statistical data analysis for ten WWER-1000 units of Ukrainian nuclear power plants has been performed to derive the relationship between the critical brittleness temperatures Тk0 (technical data on reactor pressure vessel) and Тkt (surveillance test data) for base and weld metal in unirradiated condition. According to standard PNAE G-7-002-86, there are two methods to evaluate the critical brittleness temperature of RPV materials in unirradiated (initial) condition. One method is deterministic, in which specified criteria are to be fulfilled to determine the critical brittleness temperature (Тk0). This temperature is evaluated within RPV material qualification tests. The other method employs a regression analysis of the temperature dependence of impact toughness applying a hyperbolic tangent function. In the latter case, the brittleness temperature (Тkt) is determined using the surveillance test data. The analysis has shown that Тkt increases with higher Тk0, and this correlation is linear for the examined materials. The set temperature Тk0 is 15°C higher than Тkt on average. The standard deviation for the linear correlation is 6°C. An equation to evaluate Тk0 has been proposed within this correlation analysis and can be applied to determine the critical brittleness temperature with a required safety margin for justification of WWER-1000 RPV safe operation